Determinación de alfafetoproteína y perfil hepático en pacientes alcohólicos de los centros de rehabilitación CENTSADIC, POSADA, SOLIDARIA y REMAR en la ciudad de Loja - Benalcázar Ludeña, Sthefanía Katherine (2014)
Alcoholism is a disease characterized by produce physical and psychological dependence for the use of alcohol, It interferes not only in the health, but also with social, family, economic or working responsibilities. The regular use of alcohol produces a spectrum of hepatic diseases ranging from simple esteatosis (fatty liver), to cirrhosis or even liver cáncer in the most severe cases. The present research work is aimed at determining the tumor marker alpha-fetoprotein and hepatic function tests in alcoholic patients that are in rehabilitation, with the objective to assess the hepatic function, because these tests are interrelated, in the same way, the found results were related to the consumption time and the age of starting to use alcohol. This research is descriptive and cross-sectional, which were analyzed 55 samples of alcoholic patients who were receiving care in rehabilitation centers like Centsadic, Posada Solidaria and REMAR, with due authorization from the managers. The samples were analyzed by the methods of microelisa for determining the alpha-fetoprotein and enzymatic colorimetric method for hepatic profile. The obtained data were classified according to the reference values in enhanced, normal and diminished. Thus, it was found that transaminases (TGO and TGP) were the tests that mainly were found altered by 52.8%. Respect to the alpha-fetoprotein all results were normal, with respect to the consumption time the most of the patients consumed alcohol from 11 to 20 years (40%), and according to the age of starting to use alcohol the most of patients began the consumption at the age of 10 to 15 years old (62%). Words Clave: Alphafetoprotein, Hepatic Function, Microelisa, Colorimetric Method.